Bifunctional acid–base mesoporous silica@aqueous miscible organic-layered double hydroxides. Issue 7 (28th January 2019) - Suo, Hongri; Duan, Haohong; Chen, Chunping; Buffet, Jean-Charles; O'Hare, Dermot
Abstract : Core@shell materials which exhibit hierarchical morphology with ultra high surface area and controllable pore size and structure have been synthesised. Abstract : A facile method for the synthesis of a series of mesoporous silica nanoporous (MSN) aqueous miscible organic layered double hydroxide core@shell nanocomposites using MCM-41, Al-MCM-41, SBA-15, and MCM-48 as the core is reported. These materials exhibit hierarchical morphologies with high surface areas and good porosity. Chemically, these materials offer controllable bifunctional basicity and acidity.